EPA guidance on the role and responsibilities of psychiatrists - Bhugra, D; Ventriglio, A; Kuzman, M R; Ikkos, G; Hermans, M H-M; Falkai, P; Fiorillo, A; Musalek, M; Hoschl, C; Dales, J; Beezhold, J; Rössler, W; et al. (European psychiatry, 2015)
Psychiatry is that branch of the medical profession, which deals with the origin, diagnosis, prevention, and management of mental disorders or mental illness, emotional and behavioural disturbances. Thus, a psychiatrist is a trained doctor who has received further training in the field of diagnosing and managing mental illnesses, mental disorders and emotional and behavioural disturbances. This EPA Guidance document was developed following consultation and literature searches as well as grey literature and was approved by the EPA Guidance Committee. The role and responsibilities of the psychiatrist include planning and delivering high quality services within the resources available and to advocate for the patients and the services. The European Psychiatric Association seeks to rise to the challenge of articulating these roles and responsibilities. This EPA Guidance is directed towards psychiatrists and the medical profession as a whole, towards other members of the multidisciplinary teams as well as to employers and other stakeholders such as policy makers and patients and their families.
Keywords: Responsibilities; Humans; Competencies; psychiatrie; role odborníka; Roles; Attitude to Health; postoj ke zdraví; Psychiatric Status Rating Scales; lidé; duševní poruchy; Psychiatrist; Practice Guidelines as Topic; psychiatrické posuzovací škály; směrnice pro lékařskou praxi jako téma; Mental Health Services; Mental Disorders; Psychiatry; služby péče o duševní zdraví; Professional Competence; odborná způsobilost; Risk Assessment; hodnocení rizik; Professional Role